O quotidiano de uma pessoa adulta e família que experienciam o adoecimento : contribuições para cuidar sensível em enfermagem - Sanches, Rafaely de Cassia Nogueira (2015)
This study aimed to understand how to express the quotidian elementary forms in the falling ill experience of a person with chronic condition for chronic renal failure and understanding what a young person in chronic illness situation and his family express in their quotidian´s care. It is a qualitative study Case. A Study with comprehensive approach of Michel Maffesoli. The participants of the study were: young woman in disease process by chronic condition 15 years ago, her husband and her mother. It held a total of 12 meetings from November 2014 to May 2015, using as a strategy for collecting data an interview in depth, which allowed a greater depth to the subject starting from the free speech of the person about her illness experience. As the main theoretical axis, we use the five assumptions of sensitivity from Michel Maffesoli which supported us in understanding of the experience of living and falling ill. To organize and analyze the data we used the tools of genogram and ecomap in their temporal and spatial dimensions. The discussion and analysis of the data were organized through two manuscripts: 1) The postmodern quotidian in the experience in falling ill of a person with chronic disease. After transcribing the interviews in full just like all aspects that permeated the interview´s moments with the participants of this study, the data allowed to describe two units of analysis: in the first, was built the Line of Athena's life; this analytical design was composed with events temporally listed by the participants; the second category allowed encompass the elementary forms of the quotidian in which was been discussed the Athena´s Life Line grounded in the apprehension of their quotidian.We conclude that the sensitive look about people's quotidian becomes the most suitable option for interpretation of success and /or failure of health prescriptions, highlighting the need for a deeper reflection of this new episteme, in search of offering a more careful warm, sensitive and integral. 2) The Fantastic family quotidian - the stage of the falling ill experience. We have discussed the genogram founded on the Athena´s quotidian, the intensities of their family relationships that were built along her path of becoming ill. The research glimpses a care dynamic anchored in conjunction and sensitive reason, a path able to give support to health professionals, seeking a development of the work more humanized with the families. We Apprehended in this study that to offer a care that meets the real health needs of people implies creating spaces that allow the emergency of reception and the listening, not only as privileged moments isolated, but as an intrinsic nature of the health practices, as well as the need for health professionals to understand the historical moment and their movements in which humans beings and their relationships are included in order to provide a health service that meets the needs in a holistic manner the health of people and their families. The way we conduct this research enabled us to listen attentively the experience of Athena, their fears, needs and desires.